Extra-Intestinal Manifestations of Coeliac Disease in Children: Clinical Features and Mechanisms - Nardecchia, Silvia; Auricchio, Renata; Discepolo, Valentina; Troncone, Riccardo (Frontiers in Pediatrics, 2019)
Celiac disease (CD) is considered nowadays a systemic autoimmune disease due to a dysregulated mucosal immune response to gluten and related prolamines in genetically predisposed individuals. It is a common disorder affecting approximately 1% of the general population, its incidence is steadily increasing. Changes in the clinical presentation have become evident since the 80s with the recognition of extraintestinal symptoms like short stature, iron deficiency anemia, altered bone metabolism, elevation of liver enzymes, neurological problems. Recent studies have shown that the prevalence of extraintestinal manifestations is similar between pediatric and adult population; however, specific manifestations and rate of improvement differ in the two groups and in general clinical manifestations in children seem to recede much faster than in adults. Timing of diagnosis is crucial, as an early diagnosis is decisive for a good prognosis. The pathogenesis of extraintestinal manifestations in many respects is still unclear; there are two main mechanisms probably involved, the first related to the mucosal damage and the consequent malabsorption, the second sustained by the autoimmune response. With extraintestinal manifestations dominating the clinical presentation of over half of patients, a careful case finding strategy together with a more liberal use of serological tools are crucial to improve the detection rate.